Religion and Public Life - Louay M. Safi (International Institute of Islamic Thought, 2001)
Recent developments in the political discourse on the relevance of religion to public life have reinforced the general impression, shared by scholars the world over, that religion is making a comeback to the public sphere. One example of this renewed interest in religion is the new Faith-Based and Community Initiatives, announced by President Bush. These initiatives are presented as a way to enhance the welfare and social programs of the United State government, which were challenged in the late eighties, and were seriously disrupted in the nineties. The revitalization of religion in the last few decades, and the increased recognition of the need for acknowledging the vital role played by religion and religious consciousness in maintaining the moral cohesiveness of public life, have ignited a new public debate in the West over the extent to which religion can be allowed to venture into the public square without violating the principle of separation of church and state. Muslim scholars, on the other hand, are adamant on the inseparability of religion and state in an Islamic society, where an organized religion is absent. Needless to say, such a position is usually received with great amusement and suspicion by western scholars and thinkers, often concerned about the possible stifling of the rational debate of public policy and the likely infringement of the rights of religious minorities. The conflicting positions of Muslim and western scholars is at one level a problem of incommensurability between two political cultures. On a deeper level, the incongruence between the two positions reveals a need for more profound analysis of the relevance of religion to public life in a globalizing world that is increasingly yearning for meaning and direction. Incommensurability and Political Maturation Muhyiddin Bin Arabi, the famous Andalusian Muslim mystic-scholar who lived in the fifth century of the Islamic era, (twelfth century of the Christian era), wrote the following statement in his voluminous work, Al-Futuhat a1 Makkiyyah [Makkan Insights]: ...